2017
DOI: 10.5606/tftrd.2018.1068
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blood glucose regulation on sarcopenia parameters in obese and diabetic patients

Abstract: The effect of blood glucose regulation on sarcopenia parameters in obese and diabetic patients. Turk J Phys Med Rehab 2018;64(1):72-79. ABSTRACTObjectives: This study aims to evaluate the effect of blood glucose regulation on sarcopenia parameters in sarcopenic, obese, and poorlyregulated diabetic patients. Patients and methods:Between June 2013 and December 2013, a total of 147 patients (64 males, 83 females; mean age 70.3±6.3 years; range, 60 to 90 years) who were diagnosed with sarcopenia according to the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
4
12
0
Order By: Relevance
“…Pearson or Spearman correlation analysis was used to test correlations between the variables, depending on the distribution of the parameters (r=0.00; no correlation, r=0.01-0.29 range; low level correlation, r=0.30 -0.70; medium level correlation, r=0.71 -0.99; high level correlation, r=1.00; perfect correlation). 13 A p value <0.05 was considered as statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson or Spearman correlation analysis was used to test correlations between the variables, depending on the distribution of the parameters (r=0.00; no correlation, r=0.01-0.29 range; low level correlation, r=0.30 -0.70; medium level correlation, r=0.71 -0.99; high level correlation, r=1.00; perfect correlation). 13 A p value <0.05 was considered as statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Morley and colleagues reported that the prevalence of sarcopenia was higher in diabetic than in nondiabetic individuals in Korea, India, and the UK [34]. Moreover, a previous study showed that patients with improved blood glucose regulation demonstrated improved physical functions, including gait speed and handgrip strength [35]. Abnormal fasting glucose level (>126 mg/dL) was selected as an independent predictor of sarcopenia in the TRSS model, after adjusting for history of diabetes mellitus and other comorbidities.…”
Section: The Associations Between Sarcopenia and Items From Trss Modelmentioning
confidence: 99%
“…5 Due to this important role in glucose utilization, loss of skeletal muscle mass (sarcopenia) will worsen insulin resistance (IR) in T2DM. 6 Macroautophagy (autophagy) is a process in a cell characterized by developing a closed double-membrane vesicle called the autophagosome. The autophagosome then fused with the lysosome to degrade its content.…”
Section: Introductionmentioning
confidence: 99%